Estimation of the velocity of a moving ground target using a SAR System, based on a modified multiple-measurement vector model. Issue 10 (3rd October 2017) - Chen, Yi-chang; Zhang, Qun; Yin, Yu-fu; He, Qi-fang; Li, Kai-ming
ABSTRACT: A velocity estimation method of ground moving target with sparse sampling data is proposed in this letter. Firstly, the moving target echo signal is converted to squinted synthetic aperture radar (SAR) received signal. Then, a modified multiple-measurement vector (MMV) model is built to obtain the sparse representation of ground moving target, and the improved orthogonal matching pursuit (OMP) algorithm (range migration OMP, RM-OMP) is utilized to reconstruct the coarse image of moving target. Finally, the azimuth- and range-velocity of moving target can be estimated simultaneously by searching all the possible velocity such that the minimum-entropy of coarse image is reached. Different from the homologous velocity estimation methods, the proposed method can obtain accurate estimation with signals sampled below the Nyquist rate. And benefits from the multiple measurements, the proposed method can produce better estimation accuracy and less computational complexity than the single measurement vector (SMV)-based method. The simulated data processing results validate the effectiveness of the proposed method.